Italian Chivalric Literature and Digital Humanities - Jo Ann Cavallo (Tirant)
There is an ever-growing number of Digital Humanities initiatives that explore Italian chivalric literature and its reception in the theatrical and visual arts, from combined digital and print projects that include Italian-language narratives within a panorama of world epics to interactive websites focused on a single epic text. This essay spotlights digital resources that I have found especially fruitful for the study and teaching of Italian chivalric works as well as two websites that I’m in the process of developing and other in-progress digital initiatives that have come to my attention.